2015
DOI: 10.2460/javma.246.7.754
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic influence of acepromazine or dexmedetomidine premedication in isoflurane-anesthetized dogs

Abstract: Acepromazine exacerbated hypotension, but CO did not change in dogs anesthetized with propofol and isoflurane. Dexmedetomidine reduced CO but prevented propofol-isoflurane-induced hypotension. In general, oxygen-carrying capacity and PCV were higher in dexmedetomidine-treated than in acepromazine-treated dogs anesthetized with propofol and isoflurane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 25 publications
4
23
1
4
Order By: Relevance
“…Binding to peripheral alpha1-adrenergic receptors may cause phenothiazine to induce peripheral vasodilatation, and consequently tachycardia CORTOPASSI, 2002). This was reported in dogs treated with acepromazine and anesthetized with isoflurane (MONTEIRO et al, 2007;GRASSO et al, 2015) and would corroborate the data in this study, although only the GMO group showed significant changes.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Binding to peripheral alpha1-adrenergic receptors may cause phenothiazine to induce peripheral vasodilatation, and consequently tachycardia CORTOPASSI, 2002). This was reported in dogs treated with acepromazine and anesthetized with isoflurane (MONTEIRO et al, 2007;GRASSO et al, 2015) and would corroborate the data in this study, although only the GMO group showed significant changes.…”
Section: Resultssupporting
confidence: 82%
“…Propofol can reduce SBP by 15 to 30%, and the dosedependent manner and the previous or subsequent administration of opioids may potentiate the hypotensive effect of the anesthetic (MAGELLAN; CHEIBUB, 1990). Also, in dogs anesthetized with isoflurane and treated with acepromazine, it was noted that this drug potentiated the hypotensive effects of inhalational anesthetics (MONTEIRO et al, 2007;GRASSO et al, 2015). Such observations corroborate the results of this study, indicating that the phenothiazine associated with the opioids in question may have enhanced the cardiovascular depressant effects of propofol.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…A causa da diminuição na onda A, em TA e TMA, pode ser atribuída à provável hipotenção causada pela acepromazina (Grasso et al, 2015). Com o menor aporte sanguíneo chegando ao coração, a passagem passiva do sangue do átrio esquerdo para o VE (onda E) se mantém constante, restando um menor volume para a passagem ativa (onda A), o que provoca uma diminuição na velociade máxima da onda A.…”
Section: Resultsunclassified
“…Estes achados sugerem prejuízo nos parâmetros de função sistólica quando a acepromazina foi utilizada isoladamente, podendo ser consequência da hipotensão causada por esse fármaco (Grasso et al, 2015). A hipotensão provoca diminuição do volume sanguíneo que chega ao coração, levando ao menor estiramento das fibras do miocárdio e à diminuição da força de contração, segundo a lei de Frank-Starling (Reece, 2006).…”
Section: Resultsunclassified